Analisis Kesetaraan Gender dan Inklusi Sosial Pada Program Perlindungan Sosial : Studi Kasus Bantuan Sosial Tunai Covid-19 di Kabupaten Bandung Barat - Ahmad Yaneri; Arini Dwi Deswanti (Politeknik Kesejahteraan Sosial Bandung, 2021)
The objectives of the research were to examine the experiences of groups of men and women on Sodong Village RW 15 and RW 16, Kertajaya Village, West Bandung Regency in decision making and access to cash social assistance for COVID-19 and to analyze various factors that affect their relative participation using the framework. interectionality analytic work. The research method used is in the form of qualitative methods using primary data through semi-structured interviews, FGDs and informant observations. The results showed that men and women have a significant gap in accessing health system information and social protection. The role of women is identified as a passive group in their participation. This indicates that women's groups only know about decisions that have been taken, or only attend meetings and listen to decisions. The narrative of marginalization and domination appears in this study, this is driven by a variety of cross-cutting factors such as gender, education, age, wealth, meritocracy and personality. The characteristics of marginalization in the findings of this study vary depending on the combination of sources of marginalization itself, such as someone who is elderly, uneducated, female, and poor is more marginalized than someone who is uneducated and poor but male. The more factors a person has of the character of marginalization, the greater their exclusion in accessing information on the health system and social protection of COVID-19 as a whole. This study also reveals that women experience a higher level of gender-based discrimination, especially because women are part of the dominant patriarchal system.